2000
DOI: 10.1067/mva.2000.106954
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic-assisted abdominal aortic aneurysmectomy

Abstract: Laparoscopic-assisted aneurysmectomy is safe and effective and can be performed with good results. The longer operation time required is well tolerated in patients who are at good and moderate risk. Prior training in laparoscopic aortic surgery is necessary for surgeons to obtain the required level of expertise needed to perform these procedures. With these caveats, the results of our study suggest that laparoscopic-assisted aortic aneurysmectomy is appropriate for moderate-to-good risk (American Society of An… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
35
0

Year Published

2002
2002
2012
2012

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(36 citation statements)
references
References 13 publications
1
35
0
Order By: Relevance
“…15 We had a large number of patients with calcification of the iliac arteries and aortic bifurcation. The decision about which kind of graft could be used was made intraoperatively, with respect to the time already spent for the procedure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…15 We had a large number of patients with calcification of the iliac arteries and aortic bifurcation. The decision about which kind of graft could be used was made intraoperatively, with respect to the time already spent for the procedure.…”
Section: Discussionmentioning
confidence: 99%
“…This is especially important with regard to the long-term sequelae of the surgical procedure, like adhesions and ventral hernias. [15][16][17][18] When a total laparoscopic program is started, time limits should be set to avoid problems with ischemia or blood loss. Perseverance beyond a certain point can cause harm to the patient, considering that the surgeon can be unaware of the time already spent.…”
Section: Discussionmentioning
confidence: 99%
“…These preliminary studies revealed the technical difficulties of dissection in the retroperitoneal approach (systematic division of the inferior mesenteric artery, left ureter injury, difficult control of bleeding). The greater omentum and bowel were shifted in the upper abdomen and the table tilted to 30°Trendelenburg position in the transperitoneal approach (7)(8)(9)(10)(11). However, this technique described by BARBERA et al (5) gives a lesser exposure of the aorta and the bowel retraction remains difficult, even when using fan retractors.…”
Section: Discussionmentioning
confidence: 97%
“…Laparoscopy-assisted replacement for AAA is another less invasive method. 12,13 This method requires a short abdominal incision with a length comparable with that required with the MIVS technique but requires substantial time and complicated treatment procedures. There are many problems left to be resolved with these new techniques.…”
Section: Discussionmentioning
confidence: 99%